2006
DOI: 10.3892/ijo.28.2.551
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-mediated inhibition of chemotherapy in ovarian carcinomas

Abstract: The glucocorticoid dexamethasone is frequently used as a co-treatment in cytotoxic cancer therapy, e.g. to prevent nausea, to protect normal tissue or for other reasons. While the potent pro-apoptotic properties and supportive effects of glucocorticoids to tumour therapy in lymphoid cells are well studied, the impact on the cytotoxic treatment of ovarian carcinoma is unknown. We tested apoptosisinduction, viability, tumour growth and protein expression using established cell lines, primary cell lines freshly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 17 publications
3
32
2
1
Order By: Relevance
“…The results of Wang et al 87 however, can not be explained on the basis of cell kinetics. Thus, the results from our 6,90,91,95 and other studies in murine and human tumor xenografts indicate that, in GC-sensitive tumors, concurrent treatment with steroids and anticancer drugs may be contraindicated and that the effectiveness of cycle stage-specific agents may be considerably reduced due to unfavorable cell cycle distributions. On the other hand, GCs may add significantly to the effectiveness of a sequential chemotherapy program when used appropriately by altering the temporal relationship of the recovery events in the tumor and the normal tissues.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 71%
“…The results of Wang et al 87 however, can not be explained on the basis of cell kinetics. Thus, the results from our 6,90,91,95 and other studies in murine and human tumor xenografts indicate that, in GC-sensitive tumors, concurrent treatment with steroids and anticancer drugs may be contraindicated and that the effectiveness of cycle stage-specific agents may be considerably reduced due to unfavorable cell cycle distributions. On the other hand, GCs may add significantly to the effectiveness of a sequential chemotherapy program when used appropriately by altering the temporal relationship of the recovery events in the tumor and the normal tissues.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 71%
“…A recent study reported that the systemic administration of steroids reduced chemotherapy-induced adverse effects; however, they also reduced the tumoricidal activity of the chemotherapy (Zhang et al, 2006). This limits the systemic use of steroids and favors a local administration of such drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some agents that protect hearing reduce antitumor efficacy (Zhang et al, 2006). A recent study reported that the systemic administration of steroids reduced chemotherapy-induced adverse effects; however, they also reduced the tumoricidal activity of the chemotherapy (Zhang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Be ca use of the pro-apoptotic and anti-proliferative effects in lymphoid tissues, GCs, such as the highly effec tive synt hetic agent dexamethasone (DEX), are widely used as co-medication in cancer therapy (9). The distinct effects of GCs on different tumor types have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The distinct effects of GCs on different tumor types have been reported. Contrary to the supportive action of GCs in the anti-tumor therapy of lymphomas, glucocorticoid-induced resistance toward cancer therapy is common in ova rian, lung and cervical carcinomas (9,10). A possi ble involvement of GCs in the regulation of gal-1 expression in choriocarcinoma cells has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%